1986
DOI: 10.1346/ccmn.1986.0340507
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Detrital Biotites and Their Phyllosilicate Intergrowths in Sandstones

Abstract: Abstract--Microprobe analyses of optically homogeneous detrital biotites from sandstones of the Visings6 Group and the Dala Sandstone, Sweden, revealed a consistently low K content (generally <0.75 atom/ formula unit) and variable amounts ofFe, Mg, A1, and Si. Electron probe profiles of some biotite grains indicated two major types of interstratification, one consisting of mainly illite layers and the other apparently consisting of chlorite layers. The layer thicknesses commonly ranged between 0.5 and 3 gm. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Authigenic chlorite may also develop during diagenesis as a result of the dissolution of iron-and magnesium-rich detrital grains and volcanic rock fragments (AlDahan and Morad, 1986;Anjos et al, 2000;Blackbourn and Thomson, 2000;Burns and Ethridge, 1979;De Ros et al, 1994;Remy, 1994;Thomson, 1979;Valloni et al, 1991;Worden and Morad, 2003), and from mud intraclasts (Worden and Morad, 2003), and this can lead to a wide range of chlorite compositions. The development of chlorite-coats in reservoir sands from this range of detrital grains requires at least the partial dissolution of the original grain and the neoformation of a clay mineral.…”
Section: Diagenetic Chlorite-coats Formed From the Dissolution Of Detmentioning
confidence: 99%
“…Authigenic chlorite may also develop during diagenesis as a result of the dissolution of iron-and magnesium-rich detrital grains and volcanic rock fragments (AlDahan and Morad, 1986;Anjos et al, 2000;Blackbourn and Thomson, 2000;Burns and Ethridge, 1979;De Ros et al, 1994;Remy, 1994;Thomson, 1979;Valloni et al, 1991;Worden and Morad, 2003), and from mud intraclasts (Worden and Morad, 2003), and this can lead to a wide range of chlorite compositions. The development of chlorite-coats in reservoir sands from this range of detrital grains requires at least the partial dissolution of the original grain and the neoformation of a clay mineral.…”
Section: Diagenetic Chlorite-coats Formed From the Dissolution Of Detmentioning
confidence: 99%
“…Yoneyama et al (1989) showed that anatase can occur as pillars in smectite interlayers, and Yau et al (1987) implied that anatase forms during the smectite-to-illite transformation. Chemical compositions published by Eggleton and Banfield (1985), A1-Dahan and Morad (1986), Newman (1987), Brigatti et al (1991) and Deer et al (1992) show that biotite, pyroxene and amphibole can contain up to 10% TiO2, but chlorite contains little or none (Curtis et al 1984;Whittle 1986;Hillier and Velde 1991;Jiang et al 1994). Eggleton and Banfield (1985) indicated that Ti is liberated during the retrograde metamorphic reaction of granitic biotite to chlorite, suggesting that anatase could form in sedimentary rocks during the alteration of detfital mafic minerals to chlorite or Sp/Ch.…”
Section: Introductionmentioning
confidence: 99%
“…In those laboratory experiments biotite altered to vermiculite and/or mixed-layer clay minerals. Natural weathering of biotite may also produce kaolinite, halloysite, illite, smectite, chlorite and sesquioxides (Stoch and Sikora 1976;Gilkes and Suddhiprakarn 1979;Craw et al 1982;White et al 1985;A1Dahan and Morad 1986;Morad 1990;Robertson and Eggleton 1991). In contrast to the abundant data on synthetic and natural physico-chemical weathering of micaceous minerals, the involvement of biological alteration processes is not as well understood.…”
Section: Introductionmentioning
confidence: 99%